Whither our Undergraduate Core Curriculum in Theory? - Dineen, Murray (Canadian University Music Review / Revue de musique des universités canadiennes, 1994)
In this paper, the author considers three aspects of the core curriculum: the mixture of poetics (the craft of music making) and apologetics (the argument for a canon of masterworks), the theoretical training of literate musicians, and the vehicles for bringing about curriculum change. Within this framework, the author addresses the theory text of Edward Aldwell and Carl Schachter, as well as essays by Christopher Lewis, Richard Wollheim, James Clifford, and Estelle Jorgensen. The author finds in the present curriculum an uncomfortable balance of craft and argument, and an orientation toward rote learning of a canon rather than a critical approach to knowledge skills. He finds as well little or no scholarly mechanism for curriculum development.